Overexpression of ABCC2 and NF-Κβ/p65 with Reduction in Cisplatin and 4OH-Tamoxifen Sensitivity in MCF-7 Breast Cancer Cells: The Influence of TNF-α - Nafiseh Sadat Alamolhodaei; Hatam Rashidpour; Melika Ehtesham gharaee; Javad Behravan; Fatemeh Mosaffa (Tabriz University of Medical Sciences, 2020)
Background: TNF-α, as a pro-inflammatory cytokine in the tumor microenvironment is able to regulate the expression and function of various ATP binding cassette (ABC) transporters involved in clinical drug resistance and among them, ABCC2 transporter is represented to contribute to cancer multidrug resistance (MDR) by drug efflux. Methods: In this study, we aimed to evaluate the effects of TNF-α and/or E2 (17β-estradiol) on the mRNA and protein expression levels of ABCC2 and NF-κB (p65) transcription factor in estrogen receptor positive (ER+) MCF-7 cells by QRT-PCR and Western blot analysis. Also, we used MTT assay to study the cell sensitivity against the active form of tamoxifen (4OH-TAM), a hypothetical substrate and Cisplatin (Cis), a well-known substrate for ABCC2 used in endocrine and chemo-therapy of breast cancers, respectively. Data were analyzed by one-way ANOVA and Tukey tests. Significance was considered in P-values < 0.05. Results: The expression levels of ABCC2 and the active form of NF-κB (p65) were significantly increased following 20-day concomitant treatment with TNF-α and E2, compared to untreated cells as control. Also, the viability assay showed that 20-day TNF-α+E2 treatment led to more sensitivity reduction of MCF-7 cells to Cis and 4OH-TAM compared to E2-treated and untreated cells. Conclusion: Based on our findings, there is a positive correlation between ABCC2 overexpression, over-activity of NF-ҡB/p65 and decreasing the sensitivity of MCF-7 cells to Cis and 4OH-TAM following TNF-α treatment in MCF-7 cells. Further experiments are needed to elucidate possible mechanistic relationship of these findings and their clinical significance in order to circumvent the drug-resistance in breast tumors.